Implementation of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence from an Islamic Perspective on Employee Education and Training at XYZ’s Company - A’yun, Annisa Qurrota; Yasmin, Annisa; Utari M. Noer (PT Inovasi Pratama Internasional, 2024)
The purpose of this study is to identify intelligence as a proxy for worker performance at XYZ's company from an Islamic standpoint. The three types of intelligence in question are intellectual, emotional, and spiritual. Given the increasing complexity of the industry and the globalization of business, it is critical for organizations to recognize that their most valuable resource is their workforce. Utilized by XYZ's company to assist intelligence from an Islamic perspective, particularly in integrating Islamic values, this research method involves qualitative descriptive analysis. Five informants provided information during staff interviews in the operational unit responsible for human resources, education, and training. Data were also gathered through observation and documentation. The study's findings suggest that intelligence encompasses more than just cognition; it also covers other types of intelligence including emotional and spiritual intelligence. Islamic teachings place a great emphasis on the harmony between the three forms of intellect in order to develop healthy and productive persons. This allows employers to produce workers who are not only technically proficient but also possess a strong sense of social awareness and spiritual understanding.